PERANAN GURU DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA KELAS V SDN KALIDERES 06 PAGI - Ramadhanty, Salma; Oktrifianty, Erdhita; Hasan, Najib (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The purpose of this study was to determine the teacher's role in increasing students' learning interest in class V at SDN Kalideres 06 Pagi. This research uses a type of qualitative research with a descriptive approach. Data collection techniques carried out in this study were by means of observation, interviews, documentation and questionnaires. The data sources in this study were class V teachers and fifth grade students at SDN Kalideres 06 Pagi. Data analysis techniques use the stages of data reduction, data presentation, and drawing conclusions/verification. Based on the results of the study, what was analyzed was the role of the teacher, namely as a class manager, as a motivator, and as a facilitator. In the role of the teacher to determine student learning interest by looking at several indicators including (feelings of pleasure, student interest, student attention, and student involvement). Based on the results of the study it can be concluded that the teacher's role in increasing students' learning interest in class V at SDN Kalideres 06 Pagi is in the good category. The role of the teacher given to students to increase interest in learning is by creating a conducive learning climate, arranging classroom study rooms, managing the interaction of teaching and learning activities in class, using various methods, creating competition or competition between students individually and in groups, giving value to students, holding tests, announcing learning outcomes at the end of each lesson, giving (prizes, praise, and punishments), as well as providing learning tools in the form of (RPP, syllabus and teaching materials), and providing facilities to students fairly.